Global warming or global warning? A review of urban practices for adaptation to extreme heat - Pennino, Stella (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban Practices section aims at presenting recent advancements on relevant topics that underline the challenges that the cities have to face. This note provides an overview of the challenges that global warming poses and the risks in terms of climate change that it generates for territories and cities, with a specific focus on the extreme heat phenomenon. The challenges that adaptation to exteme heat events commonly faces are outlined, and a brief review of international case studies is carried out. Finally, the results of the review are discussed highlighting some key threads of extreme heat events adaptation practices and three significant examples of adaptation in urban areas are reported, within a perspective of integration and sharing of know-how on the topic.